As(III) removal of aqueous solutions using zerovalent iron nanoparticles: The role of the UVA-Vis irradiation wavelength - Pabón Reyes, Deisy Carolina; Halac, Emilia Beatriz; Litter, Marta Irene (Elsevier Science SA, 2023)
Fil: Pabón Reyes, Deisy Carolina. Universidad Nacional de San Martín. Instituto de Investigación e Ingeniería Ambiental. - Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigación e Ingeniería Ambiental; Argentina